ELABORASI ASSESSMENT PEGAWAI DALAM PENINGKATAN KINERJA - Sholihah, Maratus; Madani, Muhlis; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2023)
This study aimed to determine the elaboration of employee assessments in improving the performance of the Makassar Social Welfare Education and Training Center (BBPPKS). This study used qualitative research with data sources consisting of primary data and secondary data. Data collection techniques used interview and observation guidelines. Data analysis techniques included data reduction, data presentation, and verification. The results of the elaboration of employee assessment in improving performance, seen from the aspect of quantity of work, showed that employees were able to produce the amount of work in accordance with the SKP (employee performance targets), although sometimes there were still targets that had not been met. Aspects of quality of work, employees provided services in accordance with performance standards and were able to produce community satisfaction. Aspects of job knowledge showed that employees had knowledge and skills regarding work, Each level of position were required to meet 20JP (Training Hours). Aspects of creativeness, cooperation, dependability, initiative and personal qualities, it could be seen that employees were able to show various good attitudes and actions according to aspects.